A change point-based analysis procedure for improving the success rate of decision-making in clinical trials with delayed treatment effects - Xie, Long-Shen; Lu, Hui (Frontiers in Pharmacology, 2023)
A delayed treatment effect is a commonly observed phenomenon in tumor immunotherapy clinical trials. It can cause a loss of statistical power and complicate the interpretation of the analysis findings. This phenomenon also poses challenges for interim analysis in the context of phase II/III seamless design or group sequential design. It has the potential to lead researchers to make incorrect go/no-go decisions. Despite its significance, rare research has explored the impact of delayed treatment effects on the decision success rate of the interim analysis and the methods to compensate for this loss. In this study, we propose an analysis procedure based on change points for improving the decision success rate at the interim analysis in the presence of delayed treatment effects. This procedure primarily involves three steps: I. Detecting and testing the number and locations of change points. II. Estimating treatment efficacy. III. Making go/no-go decisions. Simulation results demonstrate that when there is a delayed treatment effect with a single change point, using the proposed analysis procedure significantly improves the decision success rate while controlling the type I error rate. Moreover, the proposed method exhibits very little disparity compared to the unadjusted method when the proportional hazards assumption holds. Therefore, the proposed analysis procedure provides a feasible approach for decision-making at the interim analysis when delayed treatment effects are present.